2020
DOI: 10.1159/000511698
|View full text |Cite
|
Sign up to set email alerts
|

Association between Platelet-Associated Immunoglobulin G Levels and Response to Corticosteroid Therapy in Patients with Newly Diagnosed Immune Thrombocytopenia

Abstract: <b><i>Objective:</i></b> Platelet-associated immunoglobulin G (PA-IgG) refers to IgG attached to the surface of platelets, while the immature platelet fraction (IPF) reflects the state of platelet production in bone marrow. Since PA-IgG and IPF are increased in patients with immune thrombocytopenia (ITP), reflecting amounts of platelet antibodies and compensatory platelet production, respectively, we hypothesized that these laboratory findings may provide useful markers for predicting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…IgG and IgM antiplatelet antibodies can be used to diagnose ITP ( 29 ). Studies have suggested that detection of PA-IgG may provide a useful predictor of the response to first-line corticosteroid therapy for ITP ( 30 ), Our research found that PLT and IgG were significantly negatively correlated, while IgG and phylum Bacteroidetes were significantly positively correlated ( P < 0.01), suggesting that antiplatelet antibodies may reflect changes in gut microbiota to a certain extent, and also that they may participate in the pathogenesis of ITP disease via IgG. On this basis, they may be used to judge diseases and guide treatment.…”
Section: Discussionmentioning
confidence: 99%
“…IgG and IgM antiplatelet antibodies can be used to diagnose ITP ( 29 ). Studies have suggested that detection of PA-IgG may provide a useful predictor of the response to first-line corticosteroid therapy for ITP ( 30 ), Our research found that PLT and IgG were significantly negatively correlated, while IgG and phylum Bacteroidetes were significantly positively correlated ( P < 0.01), suggesting that antiplatelet antibodies may reflect changes in gut microbiota to a certain extent, and also that they may participate in the pathogenesis of ITP disease via IgG. On this basis, they may be used to judge diseases and guide treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the level of PAIgG was extremely high compared to that before treatment with LEN. Although the specificity of PAIgG for ITP is thought to be low (Kelton et al 1989;Gilli et al 2012), a recent study showed that PAIgG was significantly higher among non-responders to corticosteroids than among responders, indicating that high levels of PAIgG may have clinical significance in ITP (Saburi et al 2021). Fifth, LEN has been known to induce ITP, as described previously (Herold et al 2011;Pompa et al 2016;Meguri et al 2018;Forehand III et al 2020).…”
Section: Accepted Manuscriptmentioning
confidence: 99%